Pharmacological modulation of the ATP sensitive potassium channels during repeated coronary occlusions: no effect on myocardial ischaemia or function. Issue 4 (12th March 2004) - Lindhardt, T B; Gadsbøll, N; Kelbæk, H; Saunamäki, K; Madsen, J K; Clemmensen, P; Hesse, B; Haunsø, S
Abstract : Background: Repeated episodes of myocardial ischaemia may lead to ischaemic preconditioning. This is believed to be mediated by the ATP sensitive potassium channels. Objective: To examine the effect of pharmacological modulation of the ATP sensitive potassium channels during repeated coronary occlusions. Design: Double blind, double dummy study. Methods: 38 patients with a proximal stenosis of the left anterior descending coronary artery and no visible coronary collateral vessels underwent three identical 90 second balloon occlusions, each followed by five minutes of reperfusion. The patients were randomised to pinacidil 25 mg, glibenclamide 10.5 mg, or matching placebo 90 minutes before the start of the procedure. Myocardial ischaemia was measured by continuous monitoring of ECG ST segment changes. Changes in left ventricular function were recorded with a miniature radionuclide detector, and angina was scored on the Borg scale. Results: In all patients the first balloon occlusion led to significant ST segment elevation, a clear decrease in left ventricular ejection fraction, and angina pectoris. This response was not attenuated at the second or third balloon occlusion, either in the placebo group or in the patients pretreated with pinacidil or glibenclamide. Conclusions: Under the given experimental conditions, this randomised and double blind study did not support the view that the human myocardium has an intrinsic protective mechanism that is activated by short lasting episodes of ischaemia.